A Utilization of Choline Chloride-Based Deep Eutectic Solvent Integrated with Alkaline Earth Metal Hexahydrate in the Pretreatment of Oil Palm Fronds - New, E.K. (American Chemical Society, 2021)
Over the past decade, deep eutectic solvents (DESs) have been touted as promising reagents in biomass valorization. This study focused on the novel utilization of type II choline chloride (ChCl)-based DESs by integrating group II metal chloride hexahydrate, namely, calcium chloride hexahydrate (CaCl2·6H2O) and magnesium chloride hexahydrate (MgCl2·6H2O) as the hydrogen bond donors for the pretreatment of oil palm fronds (OPF). Under atmospheric conditions, pretreatment with ChCl:CaCl2·6H2O (125 °C and 4.5 h) resulted in dual biomass valorization effects with a delignification of 46.51, followed by xylose recovery and xylan removal at 54.12 and 78.67, respectively. Such performance of ChCl:CaCl2·6H2O as a pretreatment solvent expedited the enzymatic glucose (59.31) and total reducing sugar (63.89) conversion in the OPF at a subsequent stage. Thus, the characterizations of pretreated OPF samples endorsed the application of type II ChCl-based DESs, particularly, ChCl:CaCl2·6H2O as a propitious approach for ligno-hemicellulose removal in pretreatment. ©